Law applicable to divorce and party autonomy in European private international law - Calvo Caravaca, Alfonso-Luis; Carrascosa González, Javier (CUADERNOS DE DERECHO TRANSNACIONAL, 2022)
The Rome III Regulation (Council Regulation 1259/2010 of 20 December 2010 establishing enhanced cooperation in the area of the law applicable to divorce and legal separation) contains a new set of rules on the matter. First connecting factor to determine the law applicable to divorce is party autonomy. Divorce is governed by the law chosen by the parties. This criterion is efficient. Party autonomy leads to the law with less litigation costs for the spouses. By doing so, divorce will be granted in accordance with the expectations of the parties. The agreement the applicable law is also a contract. Accordingly, some rules govern the legal capacity, consent and formal validity of the agreement. This paper deals with the requisites of this agreement and proves that the European law maker considers that party autonomy provides efficient conflict-of-law solutions even beyond the spouses’ habitual residence. It is a sign of freedom to allow the spouses to choose the law applicable to their divorce.
Keywords: divorce; party autonomy; Rome III Regulation; international litigation